Managing a major project as an enterprise: a multi-paradigm enquiry. (1st April 2011) - Basu, Ron
This paper illustrates that a multi-paradigm approach of incorporating appropriate praxis, processes and systems of operations management in managing a major project as an enterprise leads to project excellence. The findings of this research leading to the benefits of managing a major project as an enterprise also opens the debate of a multi-paradigm enquiry between operations management systems and project management. For practitioners of major projects this paper gives implications for implementing the operational excellence concepts and systems and regular self-assessments by treating the project as an enterprise leading to sustainable outcomes.